EFFECT OF BRONCHODILATORS ON HEART RATE VARIABILITY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - H. H. Shugushev; M. V. Gurizeva; V. M. Vasilenko (Столичная издательская компания, 2015)
Aim. To study effect of long-acting theophylline (Theotard, KRKA) and combination of salmeterol and fluticasone (Seretide, GlaxoSmithKline) on heart rhythm variability (HRV) and number of arrhythmic episodes in patients with chronic obstructive pulmonary disease (COPD).Material and methods. 144 patients with COPD and 35 patients of control group were examined. The analysis of HRV and Holter monitoring were made f on 2th and 14th days.Results. Treatment with both drugs led to increase in power of low- and high frequencies and their ratio (LF/HF), decrease in rate of supraventricular and ventricular arrhythmias. Theophylline therapy raised in a number of single and pair supraventricular extrasystoles. Treatment with combination of salmeterol and fluticasone did not change a number of extrasystoles.Conclusion. Combination of salmeterol and fluticasone is more preferable as a broncholytic therapy for patients with COPD and heart rhythm disorders.